Low-intensity exercise training maintains adipokines in obese children - Kang, Sunghwun; Woo, Jinhee; Yeo, Nam-Hwoeh; Ok, Duckpil; Yoo, Jaeho; Shin, Ki Ok (Journal of Pediatric Biochemistry, 2010)
The aim of the present study is to investigate the effects of a 12 weeks low-intensity exercise training on body composition, adipokines, and growth factors in normal (NG) and obese (OG) children. Maximal oxygen uptake (VO2max); body composition; adipokines consisting of adiponectin, retinol binding protein-4 (RBP4), and interleukin-6 (IL-6); and growth factors including insulin like growth factor-1 (IGF-1) and insulin like growth factor binding protein-3 (IGF-BP3) were measured before and after low-intensity exercise training program. Body composition parameters such as body weight, body mass index, body fat (%) and VO2 max were significantly different between NG and OG. Adiponectin levels in NG were increased after 12 weeks exercise training. In addition, our results showed that the concentrations of adiponectin, RBP4, IGF-1, and IGF-BP3 in OG were higher than those of NG. Adiponectin levels were significantly correlated with body fat (r = −0.545, p = 0.001) and VO2max (r = 0.368, p = 0.032) and RBP4 levels were significantly correlated with body fat (r = 0.371, p = 0.031) in all subjects. Exercise training improved adiponectin levels in NG subjects and maintained the levels of body fat, adipokines (adiponectin, RBP4), and growth factors (IGF-1, IGF-BP3) in OG subjects. The present study revealed that regular low-intensity exercise training is strongly associated with high adiponectin levels in healthy children. However, obese children did not exhibit any changes in the levels of adipokines and maintained body composition and growth factors.
Keywords: Adipokine; obese children; adiponectin; RBP4; IGF-1; IGF-BP3; IL-6